I, Iago - Galland, Nicole; OverDrive, Inc. (2012)
The critically acclaimed author of The Fool's Tale, Nicole Galland now approaches William Shakespeare's classic drama of jealousy, betrayal, and murder from the opposite side. I, Iago is an ingenious, brilliantly crafted novel that allows one of literature's greatest villains--the deceitful schemer Iago, from the Bard's immortal tragedy, Othello--to take center stage in order to reveal his "true" motivations. This is Iago as you've never known him, his past and influences breathtakingly illuminated, in a fictional reexamination that explores the eternal question: is true evil the result of nature versus nurture or something even more complicated?
Keywords: Iago (Fictitious character) -- Fiction; Brothers -- Fiction; Murder -- Investigation -- Fiction; Cyprus -- History -- Venetian rule, 1474-1570 -- Fiction; Historical fiction; Electronic books